Environmental influences on banana shrimps of the Sofala Bank, Mozambique Channel - Malauene, Bernardino Sergio (Department of Biological Sciences, 2015)
The Sofala Bank in the western Mozambique Channel is an essential habitat for shallow-water penaeid shrimps. It supports an important multi-sector and -species fishery, with Fenneropenaeus indicus and Metapenaeus monoceros (banana shrimp) being the two main target species. Over the past decade this valuable resource has been declining, which has been attributed to environmental changes, but no conclusive evidence has been found. This PhD thesis aims to understand the interactive roles of biophysical processes on recruitment of banana shrimps, par ticularly their larvae on the Sofala Bank. It is hypothesized that shrimp larvae can be advected offshore by passing mesoscale eddies to regions where they are unable to survive and are thus lost. In the absence of both physical and biological observations, a modelling approach is used. A high-resolution, nested, coastal, Regional Ocean Modeling System (ROMS) of the Sofala Bank is developed. In general, the model agrees well with available observations and literature. The ROMS outputs and self-organizing map analysis indicate that the shelf circulation, structure and river plumes are strongly influenced by the highly energetic o_shore eddy activity. A biophysical, individual-based model (IBM) coupled to the ROMS was developed for early life stages of banana shrimps on the Sofala Bank. The IBM uses spawning patterns identified from analyses of both commercial and research survey data. Simulations indicate that shrimp larvae are lost offshore by entrainment in mesoscale eddies at inter- and intra-annual scales and eddies therefore are unlikely to produce a continuous declining in the catch. In contrast, these eddies induce onshore transport of larvae, promoting coastal settlement, compared with periods without eddies. Locations for simulated larval coastal settlement are identified: northern, central and southern. The roles of tides and larval diel vertical migration in influencing simulated larval settlement success was not conclusive; further research considering a selective tidal stream is needed. Simulated larvae were sensitive to low lethal temperature and river plumes. A conceptual model for the Sofala Bank circulation and another for the banana shrimps, early life history dynamics are proposed based on the results of this thesis.